THE CONCEPT OF ALGEBRAIC AND GEOMETRIC FUNCTIONS IN TRADITIONAL LOMBOK BALE SADE: AN ETHNOMATHEMATICS STUDY - Abdillah, Abdillah; Hadi, Alfian Rahman; Mandailina, Vera; Syaharuddin, Syaharuddin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This study aims to explore the application of the concepts of algebraic functions and geometry in the traditional architecture of Bale Sade, a traditional house of the Sasak people in Lombok, through an ethnomathematics approach. Although previous studies have highlighted geometric aspects in Sasak arts and crafts, in-depth studies of the application of algebraic and geometric principles in traditional building structures are limited. This research uses a qualitative approach with descriptive methods, through field observations in Rembitan Village, Pujut Subdistrict, interviews with several resource persons, TA (Traditional Leaders), and PW (Tour Guides), and documentation in Rembitan Village, Pujut Subdistrict, Central Lombok. Data analysis refers to the Miles and Huberman model which includes collecting, reducing, presenting data, and drawing conclusions. The results show that the structure of Bale Sade reflects mathematical principles such as symmetry, proportion, and geometric balance, as well as the application of algebra in calculating dimensions and efficient use of materials. In addition to functioning as a residence, Bale Sade reflects local wisdom that is closely related to cultural and environmental values. While previous studies have highlighted geometric aspects in the arts and crafts of the Sasak people, this study also makes an in-depth contribution to the application of algebraic and geometric principles in traditional building structures. This research recommends further studies that highlight the resilience of traditional architecture to climate change and the potential integration of modern technology in design without losing cultural values.